Nutrition Education For Pregnant Women to Reduce Anemia and Accelerate the Reduction of Stunting in Toddlers - Aritonang, Evawany Yunita; T.Sabrina; Lubis, Satia Negara; Manalu, Sarah Patumona; Yasmine Anggia Sari; T.Calysta Mauditrice; Ginting, Aisyah Amira (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Anemia and stunting are significant public health issues that require immediate attention to prevent adverse impacts on maternal and child health, as well as the overall quality of human resources. One of the leading causes of maternal mortality is iron deficiency anemia, often compounded by inadequate antenatal care (ANC). In addition, poor maternal nutritional status negatively affects pregnancy outcomes, such as low birth weight, and hinders optimal growth and development in infants—factors that contribute to the risk of stunting. In both Indonesia and Vietnam, the prevalence of anemia among pregnant women remains high, ranging between 30–40%. Similarly, the prevalence of stunting in both countries is also elevated, estimated at 20–30%. Given this situation, early intervention through nutrition education for pregnant women is crucial to improve dietary patterns that meet balanced nutritional needs. Moreover, monitoring antenatal care practices is necessary to assess the level of compliance and ensure proper pregnancy management. This community engagement activity involves collaboration with health workers from the sub-health centers (Puskesmas Pembantu) in Medan, Indonesia, and Hanoi, Vietnam, as local partners. It is expected that by empowering pregnant women through nutrition education, maternal nutritional status can be improved, thereby contributing to the fulfillment of the First 1,000 Days of Life (HPK) nutrition framework and ultimately supporting efforts to prevent stunting.